2021
DOI: 10.1101/2021.09.27.461910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AlphaFold2: A role for disordered protein prediction?

Abstract: The development of AlphaFold2 was a paradigm-shift in the structural biology community; herein we assess the ability of AlphaFold2 to predict disordered regions against traditional sequence-based disorder predictors. We find that a naive use of Dictionary of Secondary Structure of Proteins (DSSP) to separate ordered from disordered regions leads to a dramatic overestimation in disorder content, and that the Predicted Aligned Error (PAE) provides a much more rigorous metric. In addition, we show that even when … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…AlphaFold2 pLDDT not competitive as proxy for CheZOD score disorder. It has recently been suggested that AlphaFold2's pLDDT score is a reasonable indicator for disorder (Wilson et al, 2021;Piovesan et al, 2022). By plotting pLDDT against CheZOD scores (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AlphaFold2 pLDDT not competitive as proxy for CheZOD score disorder. It has recently been suggested that AlphaFold2's pLDDT score is a reasonable indicator for disorder (Wilson et al, 2021;Piovesan et al, 2022). By plotting pLDDT against CheZOD scores (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AF2 and RF are capable of predicting the 3D structures of input sequences with extremely high accuracy. Since the release of the source codes of both tools, discussions about their application limits and applicability have continued ( 18 25 ). These software tools are considered to predict homo- or hetero-complex structures as well as monomer structures, although researchers around the world are currently testing whether AF2 can predict complex structures with the same accuracy as monomeric structures.…”
Section: Introductionmentioning
confidence: 99%
“…Position-based analysis of Matrin3 disorder reveals that the region between RRM2 and ZnF2 have the highest tendency for disorder, while the region spanning the RRMs has the lowest. Considering the recent computational successes in describing the structural features and dynamics of disordered proteins ( Cino et al, 2011 ; Krzeminski et al, 2012 ; Do et al, 2014 ; Ramis et al, 2019 ; Pietrek et al, 2020 ; Wilson et al, 2021a ; Chang et al, 2021 ), molecular simulation of specific protein segments could help to more accurately characterize Matrin3, FUS, and TDP-43, by producing a structural ensemble rather than a single frame. Computational methods have also been extended to study protein aggregation propensities ( Morriss-Andrews and Shea, 2015 ), liquid-liquid phase-separation ( Paloni et al, 2020 ; Benayad et al, 2021 ), IDP-protein interactions ( Cino et al, 2013 ; Do et al, 2016 ; Karttunen et al, 2018 ), and the effects of mutation ( Vacic et al, 2012 ; Wilson et al, 2021b ) and post-translational modification ( Jin and Graeter, 2021 ; Sieradzan et al, 2021 ) on protein structure, all potential avenues for investigation of a disordered ALS protein like Matrin3.…”
Section: Structure Disorder and Llps In Matrin3mentioning
confidence: 99%